Analisis Pesan Dakwah dalam Konten Tiktok sebagai Media Komunikasi dan Penyiaran Islam - lovicandra anita; Hendra Hendra; Roy Aldiansyah; Zaini AkmalAhmad (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
This study analyzes da'wah messages in TikTok content as a medium of Islamic communication and broadcasting. The research uses a qualitative library-based content analysis by examining recent scholarly works and digital reports related to TikTok, da'wah communication, Islamic literacy, and short-video platform dynamics. The study finds that TikTok da'wah messages generally appear in three dominant categories, namely creed, worship and social ethics, and moral-spiritual motivation. The platform's short-video format encourages preachers and Islamic creators to package religious messages through concise narration, visual hooks, captions, popular sounds, hashtags, and interactive responses. TikTok offers broad opportunities for Islamic broadcasting, especially among youth audiences, but it also requires strong digital literacy, ethical communication, source verification, and sensitivity to audience diversity. The study recommends a contextual da'wah strategy that combines Islamic values, communicative creativity, platform literacy, and responsible engagement.